Usage and Dose Response of a Mobile Acceptance and Commitment Therapy App: Secondary Analysis of the Intervention Arm of a Randomized Controlled Trial - Mattila, Elina; Lappalainen, Raimo; Välkkynen, Pasi; Sairanen, Essi; Lappalainen, Päivi; Karhunen, Leila; Peuhkuri, Katri; Korpela, Riitta; Kolehmainen, Marjukka; Ermes, Miikka (JMIR Publications, 2016)
BackgroundMobile phone apps offer a promising medium to deliver psychological interventions. A mobile app based on Acceptance and Commitment Therapy (ACT) was developed and studied in a randomized controlled trial (RCT). ObjectiveTo study usage metrics of a mobile ACT intervention and dose-response relationship between usage and improvement in psychological flexibility. MethodsAn RCT was conducted to investigate the effectiveness of different lifestyle interventions for overweight people with psychological stress. This paper presents a secondary analysis of the group that received an 8-week mobile ACT intervention. Most of the analyzed 74 participants were female (n=64, 86%). Their median age was 49.6 (interquartile range, IQR 45.4-55.3) years and their mean level of psychological flexibility, measured with the Acceptance and Action Questionnaire II, was 20.4 (95% confidence interval 18.3-22.5). Several usage metrics describing the intensity of use, usage of content, and ways of use were calculated. Linear regression analyses were performed to study the dose-response relationship between usage and the change in psychological flexibility and to identify the usage metrics with strongest association with improvement. Binary logistic regression analyses were further used to assess the role of usage metrics between those who showed improvement in psychological flexibility and those who did not. In addition, associations between usage and baseline participant characteristics were studied. ResultsThe median number of usage sessions was 21 (IQR 11.8-35), the number of usage days was 15 (IQR 9.0-24), and the number of usage weeks was 7.0 (IQR 4.0-8.0). The participants used the mobile app for a median duration of 4.7 (IQR 3.2-7.2) hours and performed a median of 63 (IQR 46-98) exercises. There was a dose-response relationship between usage and the change in psychological flexibility. The strongest associations with psychological flexibility (results adjusted with gender, age, and baseline psychological variables) were found for lower usage of Self as context related exercises (B=0.22, P=.001) and higher intensity of use, described by the number of usage sessions (B=−0.10, P=.01), usage days (B=−0.17, P=.008), and usage weeks (B=−0.73, P=.02), the number of exercises performed (B=−0.02, P=.03), and the total duration of use (B=−0.30, P=.04). Also, higher usage of Acceptance related exercises (B=−0.18, P=.04) ConclusionsThe results indicated that active usage of a mobile ACT intervention was associated with improved psychological flexibility. Usage metrics describing intensity of use as well as two metrics related to the usage of content were found to be most strongly associated with improvement. Trial RegistrationClinicalTrials.gov NCT01738256; https://clinicaltrials.gov/ct2/show/NCT01738256 (Archived by WebCite at http://www.webcitation.org/6iTePjPLL)